Analisis Laporan Keuangan dengan Menggunakan Rasio Keuangan dalam Mengukur Kinerja Keuangan Pada PT PLN (Persero) Periode 2020-2023 - Yuridilla Khalnaya; Binti Shofiatul Jannah (WANARGI : Jurnal Manajemen Dan Akuntansi, 2024)
This research was conducted to determine or assess the financial performance of PT PLN (Persero) during 2020, 2021, 2022 and 2023. The method or type of research used is quantitative descriptive analysis whose data is calculated or analyzed using financial ratios consisting of liquidity ratios, solvency ratios, activity ratios, and profitability ratios. The type of data used is secondary data obtained through the financial statements of PT PLN (Persero). The results showed that through the liquidity ratio the financial performance of PT PLN (Persero) was not in good condition. The solvency ratio shows a less healthy state. The activity ratio describes a very good and efficient situation. While the profitability ratio shows an inefficient state. Thus it can be concluded that the financial performance of PT PLN (Persero) in 2020, 2021, 2022 and 2023 is in a state that is not good, less healthy or inefficient.